Determining the Role of Relationship Quality and Psychological Capital in the Resilience and Self-regulation of Women with Breast Cancer - Askari, Leila; Beigi, Ali (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The diagnosis of breast cancer in women is of particular importance due to its impact on various dimensions of life quality, including physical health, mental well-being, and social welfare. Therefore, identifying factors that influence the resilience and self-regulation of women with breast cancer has garnered researchers' attention. This study aims to investigate the role of the quality of relationships with others and psychological capital in the resilience and self-regulation of women diagnosed with breast cancer. Methodology: This research is applied in its purpose and descriptive-correlational in its method and nature. The statistical population of this study included all women with breast cancer who attended hospitals in Shahroud and Semnan. Based on the Green formula, 200 individuals were selected as the sample through purposive sampling, and research questionnaires were distributed among them. For data collection, standardized questionnaires on relationship quality by Pierce et al. (1991), psychological capital by Luthans et al. (2007), resilience by Connor and Davidson (2003), and self-regulation by Bouffard (1995) were used. Data were analyzed using SPSS software version 22 and regression analysis method. Findings: Data analysis revealed that the quality of relationships with others and psychological capital have a significant positive impact on the resilience and self-regulation of women with breast cancer (p